New Single-Year Radiocarbon Measurements Based on Danish oak Covering the Periods AD 692–790 and 966–1057. Issue 4 (12th August 2020) - Kudsk, Sabrina G K; Philippsen, Bente; Baittinger, Claudia; Fogtmann-Schulz, Alexandra; Knudsen, Mads F; Karoff, Christoffer; Olsen, Jesper
ABSTRACT: Single-year measurements of radiocarbon ( 14 C) in tree rings have led to the discovery of rapid cosmic-ray events as well as longer lasting anomalies, which have given new insights into the Sun's behavior in the past. Here, we present two new single-year 14 C records based on Danish oak that span the periods AD 692–790 and 966–1057, respectively, and consequently include the two rapid cosmic-ray events in AD 775 and 994. The new data are presented along with relevant information on the dendrochronological dating of the wood pieces, implying that these new measurements may contribute towards generating the next international calibration curve. The new data covering the AD 966–1057 period suggest that the increase in atmospheric 14 C associated with the cosmic-ray event in AD 994 actually occurred in AD 993, i.e. one year earlier than the year reported in Fogtmann-Schulz et al. (2017) based on oak from southern Denmark. Careful reanalysis of the dendrochronology that underpins the new 14 C records based on oak material from southern Denmark reveals that the cosmic-ray event reported in Fogtmann-Schulz et al. (2017) actually took place in AD 993.